Which second language learning theories underlie language courses offered by Slovene private language schools - Meznarič, Marša (Vestnik za tuje jezike, 2011)
The article deals with language courses offered by private language schools in Slovenia. It examines who the people in charge of the language schools are, what criteria new teachers have to meet to become an employee of a school, whether the methodology applied (if any) has been carefully chosen, what the teaching techniques are and who chooses them. Second language method discoveries have been subjected to perennial criticism and scepticism over the last half of century. Teachers around the globe have been confused by the constant shifts in the popularity of different methods. The article examines the consequences of the above mentioned circumstances. The 15 interviews conducted with private language schools' managers have generated valuable information on the level of professionalism in this area of business. The results have shown that most of the randomly chosen schools are managed by language professionals or by economists who employ a linguist for controlling the teaching and learning processes and that the majority of schools does adopt a particular approach or method of teaching. Teacher trainees receive a lot of support and guidance prior to teaching in a school. In most cases, teachers are free to choose techniques of teaching according to their preferences, providing the techniques are not in conflict with the general schools' principles. The criteria for employment vary considerably. Nearly all managers would employ a professional language teacher with experience only, but others demand that the teacher be a native speaker regardless of his/her education. Several stress the importance of personal characteristics and would consider employing only light-hearted and energetic teachers. Teachers' work and students' progress are often evaluated.
Keywords: zasebne jezikovne šole; Slovenia; Slovenija; tuji jeziki; zgodovinski pregledi; didactic method; didaktika; metodika